Can the exposure of Apis mellifera (Hymenoptera, Apiadae) larvae to a field concentration of thiamethoxam affect newly emerged bees?. (October 2017) - Friol, Priscila Sepúlveda; Catae, Aline Fernanda; Tavares, Daiana Antonia; Malaspina, Osmar; Roat, Thaisa Cristina
Abstract: The use of insecticides on crops can affect non-target insects, such as bees. In addition to the adult bees, larvae can be exposed to the insecticide through contaminated floral resources. Therefore, this study aimed to investigate the possible effects of the exposure of A. mellifera larvae to a field concentration of thiamethoxam (0.001 ng/μL thiamethoxam) on larval and pupal survival and on the percentage of adult emergence. Additionally, its cytotoxic effects on the digestive cells of midgut, Malpighian tubules cells and Kenyon cells of the brain of newly emerged A. mellifera bees were analyzed. The results showed that larval exposure to this concentration of thiamethoxam did not influence larval and pupal survival or the percentage of adult bee emergence. However, this exposure caused ultra-structural alterations in the target and non-target organs of newly emerged bees. The digestive cell of bees that were exposed to the insecticide exhibited a basal labyrinth without long and thin channels and compromised mitochondria. In Malpighian tubules cells, disorganized basal labyrinth, dilated mitochondria with a deformed shape and a loss of cristae, and disorganized microvilli were observed. The results showed that the exposed bees presented Kenyon cells with alterations in the nucleus and mitochondria. These alterations indicate possible tissue degeneration, demonstrating the cytotoxicity of thiamethoxam in the target and non-target organs of newly emerged bees. Such results suggest cellular organelle impairment that can compromise cellular function of the midgut cells, Malpighian tubules cells and Kenyon cells, and, consequently, can compromise the longevity of the bees of the whole colony. Highlights: Thiamethoxam, a nenonicatinoid insecticide, can affect non-target insects, as bees. It's effects on bees were investigated after exposure during the larval phase. Larval and pupal survival and percentage of emergence were not altered. Ultrastructural alterations were observed on organs of newly emerged bees. The exposure to thiamethoxam can cause cellular alterations in organs of adult bees.